2016
DOI: 10.1016/j.celrep.2016.05.039
|View full text |Cite
|
Sign up to set email alerts
|

TMEM16F Regulates Spinal Microglial Function in Neuropathic Pain States

Abstract: SummaryNeuropathic pain is a widespread chronic pain state that results from injury to the nervous system. Spinal microglia play a causative role in the pathogenesis of neuropathic pain through secretion of growth factors and cytokines. Here, we investigated the contribution of TMEM16F, a protein that functions as a Ca2+-dependent ion channel and a phospholipid scramblase, to microglial activity during neuropathic pain. We demonstrate that mice with a conditional ablation of TMEM16F in microglia do not develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 49 publications
(61 reference statements)
2
51
0
Order By: Relevance
“…Whether the alteration in the process morphology of SDH microglia contributes to subsequent proliferation and neuropathic pain induction remains unknown. 4) Given that PNI-induced pain hypersensitivity is blunted in mice lacking a molecule (P2Y12 receptor or transmembrane protein 16F) that regulates the shape of microglial processes, 29,30) it is possible that the first morphological change in SDH microglia by PNI may also have a role in subsequent microgliosis and neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the alteration in the process morphology of SDH microglia contributes to subsequent proliferation and neuropathic pain induction remains unknown. 4) Given that PNI-induced pain hypersensitivity is blunted in mice lacking a molecule (P2Y12 receptor or transmembrane protein 16F) that regulates the shape of microglial processes, 29,30) it is possible that the first morphological change in SDH microglia by PNI may also have a role in subsequent microgliosis and neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, spinally administered PPAR-γ agonist attenuated hypersensitivity in male rats 49 , contrasting the predominant role of PPAR-γ in female mice 44 . Furthermore, other studies found no differences between female and male mice in microglia-mediated hypersensitivity 17, 32 . Future research will need to clarify whether the sex-related role of glia is restricted to selected mechanisms or models of neuropathic pain and how these findings are relevant to clinical pain.…”
Section: Glia and Sex Differencesmentioning
confidence: 83%
“…( B ) Neuro-glial mechanisms in the dorsal horn spinal cord (dashed box in A): (i) CSF1 released from injured DRG neurons activates CSF1 receptor (CSF1R) in microglia 15, 16 . (ii) TMEM16F in microglia mediates their phagocytosis of GABAergic-interneuron terminals 17 . (iii) Whether monocytes infiltrate spinal cord and their relative role versus resident microglia are still unclear 22, 26, 28, 29, 32 .…”
Section: Microgliamentioning
confidence: 99%
See 2 more Smart Citations